1997
DOI: 10.3168/jds.s0022-0302(97)76257-x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Soybeans Extruded at Different Temperatures: Milk Composition and In Situ Fatty Acid Reactions

Abstract: Twenty-four multiparous Holstein cows, 4 of which were ruminally fistulated, were assigned to one of four diets containing full-fat soybeans, either raw or extruded at 120, 130, or 140 degrees C. Our hypothesis was that the extrusion of full-fat soybeans, as well as the extrusion temperature, would affect the bypass of fatty acids in the rumen and, thus, would modify the fatty acid profile of milk fat. Total mixed diets containing 23.7% soybeans (percentage of DM) were fed for 8 wk. Milk yield was lower, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 26 publications
10
108
1
1
Order By: Relevance
“…With raw linseed, Gonthier et al (2005) reported a 38% decrease of 8:0-14:0 daily output, and a 34% decrease was observed due to linseed oil (Loor et al, 2005). Similar effect was observed after soybean (Chouinard et al, 1997) or sunflower (Schingoethe et al, 1996) dietary addition. Milk FA from 6:0 to 14:0 and part of 16:0 are synthesised by the mammary gland, and increasing amounts of unsaturated fat supplement are known to inhibit the synthesis of these FA (Clapperton and Banks, 1985).…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows supporting
confidence: 57%
See 2 more Smart Citations
“…With raw linseed, Gonthier et al (2005) reported a 38% decrease of 8:0-14:0 daily output, and a 34% decrease was observed due to linseed oil (Loor et al, 2005). Similar effect was observed after soybean (Chouinard et al, 1997) or sunflower (Schingoethe et al, 1996) dietary addition. Milk FA from 6:0 to 14:0 and part of 16:0 are synthesised by the mammary gland, and increasing amounts of unsaturated fat supplement are known to inhibit the synthesis of these FA (Clapperton and Banks, 1985).…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows supporting
confidence: 57%
“…The relative increase in milk was over 40% for trans-6 to trans-11 18:1 and cis-15 18:1, but was only 18% for trans-15 18:1, and around 10% for trans-12 and trans-16 18:1. Extrusion of oilseeds is known to result in increased proportions of trans intermediates in milk fat (Chouinard et al, 1997;Chouinard et al, 2001) but our results show that the effects differ according to the trans-18:1 isomer, suggesting that extrusion affects the pathways of ruminal BH.…”
Section: Conjugated Linoleic and Linolenic Acids In The Milk Of Cows contrasting
confidence: 52%
See 1 more Smart Citation
“…In the present study, the concentration of C18:3 was higher in silage than in fresh grass. No trans isomers of C18:2 or C18:1 were detected in silage, even though the method used allowed the detection of these fatty acids (Chouinard et al 1997), which indicates a low rate of unsaturated FA biohydrogenation during silage fermentation.…”
Section: Conservation Methods (Experiments 2)mentioning
confidence: 96%
“…Soy, a common component of dairy cattle diet, is a rich source of energy due to its high contents of proteins and oil (Chouinard et al 1997). In addition to these important nutrients, soy-based Figure 3.…”
Section: Phytoestrogens In Biological Samplesmentioning
confidence: 99%